The impact of a training curriculum to develop speed endurance in passing the readiness test during the competition period for the arena referees of the - Abdul Kareem, Mustafa; qasim, Sabah (Journal of Physical Education, 2023)
The speed of performance has become one of the most important requirements of modern football, taking into account the large area of its field of play, and in order for the football referee, who is one of the pillars of this game, to successfully lead the match, he must have high physical fitness, which also enables him to pass Physical tests that he undergoes during the sports season, as well as high performance during the match. The importance of the research is highlighted by the preparation of a training curriculum to develop the physical performance of the referees of the Iraqi Premier Football League (yard referees) during the competition period. The problem centered on the study is that most of the referees have a problem in preparing for the physical tests during the downtime between the first and second phase of the league (home and away), and most of the referees train throughout the football season on the running track for athletics and stay away from the real test of the referee, which is the field of play, so the application Standardized secondary tests approved by the International Federation of Football Associations and the use of the playing field for physical testing will inevitably contribute to changing the method of training during the competition period and avoiding the negative situations that accompany this period of physical pressure in training and the large number of injuries among referees. The research aimed to prepare a training curriculum and identify the impact of the curriculum on passing the readiness tests for the arena referees for the Iraqi Premier Football League. The researchers used the experimental method with one group due to its suitability to the nature of the problem of the study, and they chose the research sample from the arena referees for the Premier League, the first division in Baghdad Governorate, and their number was (15) referees, representing 50% of the research community, and special tests were conducted on them in the stadiums of the Ministry of Youth and Sports / Baghdad, and after analyzing And discussing the results, the researchers found that there are significant differences between the pre and posttests and in favor of the post tests of the research group because of the methodology used.